Threat impact analysis to air traffic control systems through flight delay modeling. (December 2021) - Zeng, Leya; Wang, Buhong; Tian, Jiwei; Wang, Zhen
Highlights: Modeling the air traffic control system from the perspectives of air and ground. A clear metric to assess the magnitude of the threat impact. Analysis can be done separately or simultaneously at different levels. Path rerouting, path selection, and speed change enhance the reality of the model. Abstract: Air traffic control (ATC) systems increasingly rely on communication, navigation, and other emerging digital technologies, making them more susceptible to external threats. To better analyze the different impacts, this paper proposes a new flight delay model that models the ATC system from two perspectives. In the air delay, we view the problem as an optimal path choice with a set of capacity constraints and consider the speed change, rerouting, and pathfinding. In the ground delay, the concept of cellular automata is extended to model the flight queue at each airport. Last, the system dynamics of delays are considered, and the two stages of modeling are combined using flight delay as an indicator to achieve an intuitive description of the impact on the system threat. Compared to the current state of the art, the model is shown to be a simple way to analyze the impact of different sophisticated threats. It also helps aviation system planners better understand the impact of different threats so that effective measures can be taken to improve system performance.